2011
DOI: 10.1080/02640414.2011.587442
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of anthropometric and training characteristics of Ironman triathletes and Triple Iron ultra-triathletes

Abstract: We examined differences in anthropometry and training between 64 Triple Iron ultra-triathletes competing over 11.4 km swimming, 540 km cycling, and 126.6 km running, and 71 Ironman triathletes competing over 3.8 km swimming, 180 km cycling, and 42.2 km running. The association of anthropometry and training with race time was investigated using multiple linear regression analysis. The Triple Iron ultra-triathletes were smaller (P < 0.05), had shorter limbs (P < 0.05), a higher body mass index (P < 0.05), and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 30 publications
(44 reference statements)
0
43
0
1
Order By: Relevance
“…Indeed, training for an Ironman triathlon is very demanding and in order to place in the top ten of an age group category, extremely high training volumes and intensities are required. [18,107,108,109] However, it has been suggested that masters athletes could optimize their quality of training, so they could reduce their training volume to save time for adequate recovery and remain injury free. [84] These studies suggest that masters triathletes have probably not reached their limits in ultra-endurance performance.…”
Section: Improvements In Triathlon Performance Of Elderly Triathletesmentioning
confidence: 99%
“…Indeed, training for an Ironman triathlon is very demanding and in order to place in the top ten of an age group category, extremely high training volumes and intensities are required. [18,107,108,109] However, it has been suggested that masters athletes could optimize their quality of training, so they could reduce their training volume to save time for adequate recovery and remain injury free. [84] These studies suggest that masters triathletes have probably not reached their limits in ultra-endurance performance.…”
Section: Improvements In Triathlon Performance Of Elderly Triathletesmentioning
confidence: 99%
“…In addition, the distances differ enormously between the single competitions. Much more endurance, training, and mental strength is required for a successful finish in a Double Deca Iron ultra-triathlon than for the ten-times shorter Double Iron ultra-triathlon (Knechtle, Duff, Amtmann & Kohler 2008a, Knechtle, Schwanke, Knechtle, & Kohler 2008c, Knechtle, Knechtle, Rüst & Rosemann 2011a, Lepers, Knechtle, Knechtle & Rosemann 2011, Zaryski & Smith 2005. Thus, a Triple Iron ultra-triathlete has to train for more hours than an Ironman-triathlete to reach the same level of performance (Knechtle, Knechtle, Rüst, & Rosemann 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a Triple Iron ultra-triathlete has to train for more hours than an Ironman-triathlete to reach the same level of performance (Knechtle, Knechtle, Rüst, & Rosemann 2011a). However, the average Triple Iron ultra-triathlete trains already for 19.3 hours a week (Knechtle, Knechtle, Rüst & Rosemann 2011a). Therefore, only a few ultra-triathletes of a very high level are able to complete an ultra-triathlon longer than a Triple Iron ultra-triathlon distance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations